Modification of electrical properties of the Au/1,1? dimethyl ferrocenecarboxylate/n-Si Schottky diode - Aydin, M. Enver; Yakuphanoğlu, Fahrettin; Ozturk, Gulsen (Elsevier Science Sa, 2010)
The electrical and interface state density properties of the Au/1,1' dimethyl ferrocenecarboxylate (DMFC)/n-Si structure have been investigated by current-voltage, capacitance-voltage and conductance-frequency methods. The Au/DMFC/n-Si structure exhibits a rectifying behavior with a non-ideal I-V behavior with an ideality factor greater than unity. The ideality factor and barrier height of the Au/DMFC/n-Si Schottky diode is lower than that of Au/n-Si Schottky diode. The interface state density of the diode was determined from G/omega-f plots and was of order of 5.61 x 10(12) eV(-1) cm(-2). It is evaluated that the electrical properties of Au/n-Si diode is controlled using 1' dimethyl ferrocenecarboxylate organic layer and in turn, Au/DMFC/n-Si structure gives new electronic parameters. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Organic Schottky diode; Interface properties